Pengaruh Kebijakan Dividen, Profitabilitas, Likuiditas dan Struktur Modal terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Hermawan Kustanta, Hermawan Kustanta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to test whether dividend policy, profitability, liquidity, capital structure have a partial influence on company value, as well as whether company size is able to moderate the relationship of dividend policy variables, profitability, liquidity, capital structure to company value. This study took a sample of companies going public in the telecommunications and utilities sectors listed on the IDX. The sampling technique uses purposive sampling by collecting data in the form of annual financial statements in accordance with the required criteria obtained from the official IDX website www.idx.co.id, www.emiten.kontan.co.id and other websites related to sample companies. The amount of research data processed was 240 data, with 40 data on each variable. Data was analyzed using SPSS. The results showed that dividend policy has a positive and significant influence on the value of the company; profitability and liquidity have no partial influence on the value of the company; capital structure has a negative and significant influence on the value of the company; company size moderates the relationship of dividend policy and profitability partially to company value; The size of the company does not partially moderate the relationship of liquidity and capital structure to the value of the company.